Quinolyl-functionalised Cp-chromium polymerisation catalysts: synthesis and crystal structures of alkylation products - Enders, Markus; Fernández, Pablo; Mihan, Shahram; Pritzkow, Hans (Journal of organometallic chemistry, 2003)
The quinolyl-functionalised Cp-chromium(III) complexes 1 and 2, which serve as precursors for highly active olefin polymerisation catalysts, were alkylated with benzylmagnesium chloride. From these reactions, the new metal complexes 4, 5 and 6 were obtained and structurally characterised. The expected alkylchromium compound 4 is formed together with complex 5, where the nucleophile replaced a hydrogen atom at the quinoline substituent. The dinuclear complex 6 is formed by nucleophile addition, rearrangement and dimerisation.
Available online 26 September 2003
Gesehen am 18.11.2022